New Directions in Women, Peace and Security - Basu, Soumita; Kirby, Paul C.; Shepherd, Laura C. (Bristol University Press, 2020)
Available Open Access under CC-BY-NC-ND licence. The Women, Peace and Security (WPS) agenda is rooted in international law - notably international humanitarian law, human rights and international criminal law. UNSCR 1325 specifically calls upon states to respect fully the obligations within these laws, including the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). Subsequent WPS resolutions emphasize the need for commitment to women's human rights and implementation of human rights law, without again referencing CEDAW until Resolution 2467 in April 2019. Despite the evident association of subject matter, the first seven WPS resolutions after 1325 are surprisingly silent about trafficking in women and girls, including in armed conflict. Resolution 2467 does refer to trafficking in persons but only to ask the Security Council Counter- Terrorism Committee Executive Directorate to include in its country reports information about states' efforts to address it. This does not comprehensively locate trafficking within the WPS agenda.